Augmented Reality Navigation Using Android - Akhirruddin, Mu'az Suffyan; Mohamad, Shamsul; Rafizah Mohd Hanifa (Evolution in Electrical and Electronic Engineering, 2024)
Augmented Reality (AR) navigation refers to the use of AR technology to track movement while moving in real-world environments. Traditional navigation methods often rely on maps or GPS-based instructions, which can be cumbersome and less intuitive. The AR navigation system aims to overcome these limitations by overlaying virtual directions and visual cues onto the real-world view captured by the device’s camera. The development process involves designing user-friendly interfaces, integrating location services, implementing real-time object recognition algorithms, and utilizing Android’s built-in mapping and navigation functionalities. The objectives of the work are to design mapping of QB block, to design AR real-time movement tracking, and to evaluate its accuracy, usability, and reliability by conducting user testing and collecting feedback. Unity was used to create 3D mapping of the QB block and scene setup to generate a minimap that does real-time tracking. It has a 70% accuracy rate after a few tests. In conclusion, the system is considered successful because it managed to accomplish all three objectives.